Delayed Diaphragmatic Herniation Masquerading as a Complicated Parapneumonic Effusion - John Tsang; Frank Ryan (Canadian Respiratory Journal)
Injury to the diaphragm following blunt or penetrating thoraco-abdominal trauma is not uncommon. Recognition of this important complication of trauma continues to be a challenge because of the lack of specific clinical and plain radiographic features, the frequent presence of other serious injuries and the potential for delayed presentation. Delayed diaphragmatic herniation often presents with catastrophic bowel obstruction or strangulation. Early recognition of diaphragmatic injury is required to avoid this potentially lethal complication. The case of a 35-year-old man with a history of a knife wound to the left flank 15 years previously, who presented with unexplained acute hypoxemic respiratory failure and a unilateral exudative pleural effusion that was refractory to tube thoracostomy drainage, is reported. After admission to hospital, he developed gross dilation of his colon; emergency laparotomy revealed an incarcerated colonic herniation into the left hemithorax. Interesting clinical features of this patient's case included the patient's hobby of weightlifting, a persistently deviated mediastinum despite drainage of the pleural effusion and deceptive pleural fluid biochemical indices.